PENGARUH PENERAPAN GOOD GOVERNANCE DAN STANDAR AKUNTANSI PEMERINTAHAN TERHADAP KUALITAS INFORMASI KEUANGAN PADA BADAN KEUANGAN PROVINSI GORONTALO - Saprudin (International Interdisciplinary Conference on Sustainable Development Goals, 2018)
The purpose of this research is 1) to analyze the influence of good governance implementation to the quality of financial information on the department of finance Gorontalo Province, 2) to analyze the influence of Governmental Accounting Standards to the quality of financial information on the Department of Finance Gorontalo Province. The type of this research is quantitative descriptive. The characteristic of this research is explanatory research. The population in this research amounted to 100 people. This research uses the Stratified Random Sampling method by doing data homogeneity according to the groups of fields in the Department of Finance Gorontalo Province. Data collection techniques were carried out by interview, a list of questions. The data analysis method used is Multiple Regression with SPSS program. The results of the research show that Good Governance has a positive effect, however not significant to the quality of financial information. Besides, for Governmental Accounting Standards have a positive and significant effect on the quality of financial information. The result of coefficient of determination test show that the quality of financial information in Department of Finance Gorontalo Province influenced by good governance variables and Governmental Accounting Standards of 52.9% and the remaining 47.1% influenced by other variables which have not been studied in this research among others human Resources, internal control, and technology utilization. For good governance variables to be paid more attention, especially for community participation in this case still lacking, therefore it will have an impact on the quality of financial information because, with a good implementation of good governance, it will produce good quality financial information for government agencies. For Governmental Accounting Standards variables. For government accounting standards variables must be considered, especially on the application of the accrual basis due to the application of the accrual basis recently implemented since 2015. Therefore, the staff's readiness is indispensable in order to produce good quality financial information